1995
DOI: 10.1111/j.1365-2125.1995.tb05803.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute effects of ANP and BNP on hypoxic pulmonary vasoconstriction in humans.

Abstract: 1 Atrial natriuretic peptide (ANP) and brain natriuretic peptide (BNP) have pulmonary vasorelaxant activity with plasma concentrations being elevated in patients with hypoxaemic pulmonary hypertension. However, their effects on acute hypoxic pulmonary vasoconstriction (HPV), the initiating stimulus for pulmonary hypertension have not to date been investigated. We have therefore studied the effects of ANP and BNP on acute HPV in humans. 2 Eight healthy volunteers were studied on three separate occasions. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0
2

Year Published

1997
1997
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 28 publications
1
16
0
2
Order By: Relevance
“…Consequently, BNP is a vasodilator in various tissues [11]. The intravascular application of exogenous BNP has been shown to blunt acute hypoxic pulmonary vasoconstriction in rat lungs [12] and healthy volunteers [13]. In addition, M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, BNP is a vasodilator in various tissues [11]. The intravascular application of exogenous BNP has been shown to blunt acute hypoxic pulmonary vasoconstriction in rat lungs [12] and healthy volunteers [13]. In addition, M A N U S C R I P T…”
Section: Introductionmentioning
confidence: 99%
“…Although a direct BNP induced vasodilation has never been described in a quasi in vivo setting in non hypoxia mediated pulmonary vasoconstriction, this observation is in accordance to the previously reported data from acute and chronic hypoxia. For example, intravascular application of BNP partially antagonised acute hypoxia induced pulmonary vasoconstriction in an experimental study [21] and in healthy volunteers [13]. In addition, mice lacking the natriuretic peptide A receptor encoding gene have an increased susceptibility to hypoxia mediated pulmonary vascular remodelling [22].…”
mentioning
confidence: 99%
“…It was reported that BNP was related to PASP in primary PH (Leuchte et al, 2004), and a supplementary dose of BNP reduces PASP levels (Cargill and Lipworth, 1995). BNP is a sensitive and specific predictor of LV systolic failure (Vasan et al, 2002), a very useful tool to confirm LV diastolic dysfunction (LVEF ≥ 45-50%) (Wei et al, 2005) and is in accordance with volume overload (Kunii et al, 2003) at the same time.…”
Section: Discussionmentioning
confidence: 81%
“…BNP вызывают расслабление гладких мышц со судов, что приводит к снижению давления крови и постнагрузки желудочков [22][23][24].…”
Section: Discussionunclassified
“…В пред ставленном исследовании у больных ХОБЛ даже без признаков ЛГ концентрация BNP в плазме была вы ше по сравнению со значением этого показателя у лиц, не страдавших легочно сердечной патологи ей [31]. Представляют интерес результаты ранее про веденных исследований, которые показали роль гипоксии [22,25,32,33], уровня эндотелина 1 [26], С реактивного белка [34], интерлейкина 6 [35] в по вышении концентрации BNP в плазме крови.…”
Section: Discussionunclassified